A new genus and species of giant mealybugs (Hemiptera: Coccomorpha: Monophlebidae) from eastern China - Li, Jiani; Xu, Han; Wu, San-An (Zootaxa, 2023)
A new genus of giant mealybugs (Hemiptera: Coccomorpha; Monophlebidae), Coronaproctus Li, Xu & Wu gen. nov., is established for the species Coronaproctus castanopsis Li, Xu & Wu sp. nov., collected from Zhejiang province, China on the twigs of Castanopsis eyrei (Fagaceae). The adult female and male are described and illustrated. The new genus is characterized by the adult female possessing quadrilocular disc pores, 13 cicatrices on the venter, and a U-shaped opening of the marsupium, but lacking large bilocular pores.